ANALYSIS OF GRAMMATICAL ASPECTS OF THE TALK SHOW SENTILAN SENTILUN EDITION “DPR LIBRARY FOR WHOM?” - Juni Mahsusi; Baiq Yulia Kurnia Wahidah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Abstract This study aims to determine what grammatical aspects are used in the Sentilan Sentilun discourse